Out in Culture : Gay, Lesbian and Queer Essays on Popular Culture - Doty, Alexander; Creekmur, Corey K. (Book collections on Project MUSE., 1995)
This book charts some of the ways in which lesbians, gays, and queers have understood and negotiated the pleasures and affirmations, as well as the disappointments, of mass culture. The essays collected here, combining critical and theoretical works from a cross-section of academics, journalists, and artists, demonstrate a rich variety of gay and lesbian approaches to film, television, popular music, and fashion.